Flight and seizure motor patterns in Drosophila mutants: simultaneous acoustic and electrophysiological recordings of wing beats and flight muscle activity. - Iyengar, A.; Wu, C.F. (Journal of Neurogenetics, 2014)
Tethered flies allow studies of biomechanics and electrophysiology of flight control. We performed microelectrode recordings of spikes in an indirect flight muscle (the dorsal longitudinal muscle, DLMa) coupled with acoustic analysis of wing beat frequency (WBF) via microphone signals. Simultaneous electrophysiological recording of direct and indirect flight muscles has been technically challenging; however, the WBF is thought to reflect in a one-to-one relationship with spiking activity in a subset of direct flight muscles, including muscle m1b. Therefore, our approach enables systematic mutational analysis for changes in temporal features of electrical activity of motor neurons innervating subsets of direct and indirect flight muscles. Here, we report the consequences of specific ion channel disruptions on the spiking activity of myogenic DLMs (firing at ?5 Hz) and the corresponding WBF (?200 Hz). We examined mutants of the genes enconding: 1) voltage-gated Ca(2+) channels (cacophony, cac), 2) Ca(2+)-activated K(+) channels (slowpoke, slo), and 3) voltage-gated K(+) channels (Shaker, Sh) and their auxiliary subunits (Hyperkinetic, Hk and quiver, qvr). We found flight initiation in response to an air puff was severely disrupted in both cac and slo mutants. However, once initiated, slo flight was largely unaltered, whereas cac displayed disrupted DLM firing rates and WBF. Sh, Hk, and qvr mutants were able to maintain normal DLM firing rates, despite increased WBF. Notably, defects in the auxiliary subunits encoded by Hk and qvr could lead to distinct consequences, that is, disrupted DLM firing rhythmicity, not observed in Sh. Our mutant analysis of direct and indirect flight muscle activities indicates that the two motor activity patterns may be independently modified by specific ion channel mutations, and that this approach can be extended to other dipteran species and additional motor programs, such as electroconvulsive stimulation-induced seizures.